ERECTA receptor-kinases play a key role in the appropriate timing of seed germination under changing salinity. (24th August 2019) - Nanda, Amrit K; El Habti, Abdeljalil; Hocart, Charles H; Masle, Josette
Abstract: Appropriate timing of seed germination is crucial for the survival and propagation of plants, and for crop yield, especially in environments prone to salinity or drought. However, the exact mechanisms by which seeds perceive changes in soil conditions and integrate them to trigger germination remain elusive, especially once the seeds are non-dormant. In this study, we determined that the Arabidopsis ERECTA (ER), ERECTA-LIKE1 (ERL1), and ERECTA-LIKE2 (ERL2) leucine-rich-repeat receptor-like kinases regulate seed germination and its sensitivity to changes in salt and osmotic stress levels. Loss of ER alone, or in combination with ERL1 and/or ERL2, slows down the initiation of germination and its progression to completion, or arrests it altogether under saline conditions, until better conditions return. This function is maternally controlled via the tissues surrounding the embryo, with a primary role being played by the properties of the seed coat and its mucilage. These relate to both seed-coat expansion and subsequent differentiation and to salinity-dependent interactions between the mucilage, subtending seed coat layers and seed interior in the germinating seed. Salt-hypersensitive er105, er105 erl1.2, er105 erl2.1 and triple-mutant seeds also exhibit increased sensitivity to exogenous ABA during germination, and under salinity show an enhanced up-regulation of the germination repressors and inducers of dormancy ABA-insensitive-3, ABA-insensitive-5, DELLA-encoding RGL2, and Delay-Of-Germination-1 . These findings reveal a novel role of the ERECTA receptor-kinases in the sensing of conditions at the seed surface and the integration of developmental, dormancy and stress signalling pathways in seeds. They also open novel avenues for the genetic improvement of plant adaptation to changing drought and salinity patterns. Abstract : The ERECTA family of receptor-kinases regulates seed germination in Arabidopsis under salinity, through mucilage and maternally mediated sensing of conditions at the seed surface and interactions with dormancy mechanisms.